Preparation method for plating DLC + AR film on chalcogenide glass substrate
By plating DLC and AR film layers on the sulfur-based glass substrate, the difficulty of plating DLC film on the sulfur-based glass is solved, and high transmittance and multi-environmental adaptability are achieved, meeting the use needs of window sheets.
Patent Information
- Application Number
- CN202411781517.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-25
AI Technical Summary
In the field of infrared optical coating, it is difficult to plating diamond-like (DLC) films on sulfur-based glass, and it is difficult to meet the requirements for use as window sheets in various environments.
A method for plating DLC+AR film with sulfur-based glass substrate is adopted. The DLC film layer is plated on the convex surface of the lens of the sulfur-based glass substrate and the anti-reflection (AR) film layer is plated on the concave surface. The specific steps include technical means such as cleaning, vacuum coating machine processing, electron beam evaporation and resistance heating evaporation.
The average transmittance of the sulfur-based glass substrate plating sheet and the film on both sides in the 8-12μm band is greater than 91%, and the window sheets are used through various environmental tests (such as blisters, salt spray, hot and cold shock, etc.) is met.
Smart Images

Figure CN119506787A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of optical coating, and more specifically to a method for preparing a DLC+AR film coated on a chalcogenide glass substrate. Background Art
[0002] In the field of infrared optical coating, chalcogenide glass has high processing efficiency and can be precisely molded, which is more than 10 times higher than diamond turning, and the raw material cost is 1 / 3 of that of germanium single crystal. It is suitable for temperature difference environments ranging from -40 degrees Celsius to +70 degrees Celsius, and has excellent temperature adaptability. Chalcogenide glass is widely used in infrared technology, such as infrared night vision, infrared temperature measurement, and infrared thermal imaging. Its high refractive index and low dispersion coefficient make it important in the fields of optical communications and optical sensing. The problem that plagues the optical coating industry is to coat diamond-like carbon (DLC) film on chalcogenide glass. Chalcogenide glass lenses can replace germanium lenses when used in window pieces. Summary of the invention
[0003] In view of the problems existing in the background technology, an object of the present disclosure is to provide a method for preparing a DLC+AR film coated on a chalcogenide glass substrate, wherein the transmittance of the chalcogenide glass substrate and the films on both sides thereof in the 8-12 μm band is greater than 91% on average.
[0004] Another object of the present disclosure is to provide a method for preparing a DLC+AR film coated on a chalcogenide glass substrate, wherein the prepared accompanying coating sheet of the chalcogenide glass substrate together with the film system on both sides can meet the requirements of being used as a window sheet in various environments and meet the requirements of the application end.
[0005] Therefore, a method for preparing a DLC+AR film coated on a chalcogenide glass substrate comprises the steps of:
[0006] S1, coating a DLC film layer, including sub-steps:
[0007] S11, for the coating of chalcogenide glass substrate and lens products as lenses
[0008] Clean the convex surface of the DLC film layer;
[0009] S12, placing the cleaned lens into a fixture with the convex surface facing downward, and hanging the fixture with the lens placed into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 130°C;
[0010] S13, the vacuum coating machine is started, vacuumed and heated, and the temperature of the cavity reaches the set temperature of the cavity and is kept constant for 2 hours. After that, the vacuum degree reaches 1.5×10 -3When Pa, the Hall ion source of the vacuum coating machine was turned on for cleaning. The cleaning time was 6 min. The anode voltage of the Hall ion source was 220 V, the anode current was 1.2-1.5 A, the neutralization current was 1.3-1.5 A, the neutralization gas flow rate was 10 sccm, and the argon gas flow rate accounted for 100%;
[0011] S14, vacuum degree reaches 1.0×10 -3 When the temperature is 0.504°C, a dielectric layer consisting of 291nmGe / 144nmZnS / 671nmGe is deposited on the convex surface of the lens in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers. The Ge film layer is evaporated by electron beam, and the ZnS film layer is evaporated by resistance heating. The deposition rate of the Ge film layer is 0.4nm / s, and the deposition rate of the ZnS film layer is 0.8nm / s. The film layers of the dielectric layer are not deposited by ion source assistance and are deposited at the set temperature of the chamber.
[0012] S15, after the dielectric layer is plated, the cavity is naturally cooled to below 60°C, and the fixture and the lens are taken out;
[0013] S16, placing the lens on the bottom plate of the carbon film machine with the convex surface facing upward;
[0014] S17, carbon film machine vacuum reaches 1.2×10 -3 Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3min, the argon flow rate of the RF ion source is 20sccm, and the power is 600-700W;
[0015] S18, carbon film machine vacuum reaches 6.0×10 -4 Pa starts to deposit DLC film layer, using three-stage deposition.
[0016] The first stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 500s, the RF power supply is started, the RF power supply power is 1200W, and the deposition time is 1400s.
[0017] The second stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 1000s, the RF power supply is started, the RF power supply power is 1000W, and the deposition time is 1400s.
[0018] The third stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 1500s, the RF power supply is started, the RF source power is 800W, and the deposition time is 1400s;
[0019] After the three stages were completed, the thickness of the DLC film was 1280nm;
[0020] S19, after the DLC film is coated, the carbon film machine is cooled for 50-60 minutes, and the door is opened to take out the lens; S2, AR film coating, including sub-steps:
[0021] S21, cleaning the accompanying plated sheet of the chalcogenide glass substrate on which the DLC film layer has been coated on the convex surface of the lens and the surface of the lens product corresponding to the concave surface of the lens;
[0022] S22, placing the cleaned lens into a fixture with the concave surface facing downward, and hanging the fixture with the lens placed into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 130°C;
[0023] S23, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches 1.5×10 -3 Pa and the temperature of the chamber reaches the set temperature, turn on the Hall ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2-1.5A, the neutralization current is 1.3-1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%;
[0024] S24, vacuum degree reaches 1.0×10 -3 Pa, 32 layers are plated on the concave surface of the lens.
[0025] An AR film composed of 3nmGe / 250nmZnS / 395nmGe / 741nmZnS / 350nmYbF3 / 285nmZnS, wherein the numbers with nm before Ge, ZnS and YbF3 are the thickness of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer and the YbF3 film layer are evaporated by resistance heating, the deposition rate of the Ge film layer is 0.3nm / s, the deposition rate of the ZnS film layer is 0.8nm / s, and the deposition rate of the YbF3 film layer is 0.6nm / s, and the film layers of the AR film are not deposited by ion source assistance and are deposited at the set temperature of the chamber;
[0026] S25, after the dielectric layer is plated, the cavity is naturally cooled to below 60°C, and the fixture and the lens are taken out.
[0027] The beneficial effects of the present disclosure are as follows: In the preparation method of coating DLC+AR film on chalcogenide glass substrate according to the present disclosure, through step S1 and step S2, by coating Sub (chalcogenide glass substrate) / Ge / ZnS / Ge / DLC / AIR (air) film system on the convex surface of the lens of chalcogenide glass substrate (i.e. coating DLC) and coating Sub (chalcogenide glass substrate) / Ge / ZnS / Ge / ZnS / YbF3 / ZnS / AIR (air) on the concave surface of the lens of chalcogenide glass substrate. The film system (i.e., AR film), as verified by the test process, the chalcogenide glass substrate together with the film systems on both sides can not only achieve an average transmittance of more than 91% (specifically 91.19%) in the 8-12μm band, but also pass the blister test, salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, constant temperature and humidity test, friction resistance test (moderate friction test), low temperature test and high temperature test, so that it can be used as a window piece in various environments and meet the requirements of the application end. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic structural diagram of a chalcogenide glass substrate and the film systems on both sides prepared according to the method for preparing a DLC+AR film coated on a chalcogenide glass substrate disclosed in the present invention.
[0029] Figure 2 It is a transmittance curve of the accompanying coating sheet of Example 1 together with the DLC+AR films on both sides in the 8-12 μm band. DETAILED DESCRIPTION
[0030] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0031] [Preparation method of DLC+AR film coated on chalcogenide glass substrate]
[0032] Reference Figure 1 According to the present invention, the method for preparing a DLC+AR film coated on a chalcogenide glass substrate comprises the following steps:
[0033] S1, coating a DLC film layer, including sub-steps:
[0034] S11, for the coating of chalcogenide glass substrate and lens products as lenses
[0035] Clean the convex surface of the DLC film layer;
[0036] S12, placing the cleaned lens into a fixture with the convex surface facing downward, and hanging the fixture with the lens placed into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 130°C;
[0037] S13, the vacuum coating machine is started, vacuumed and heated, and the temperature of the cavity reaches the set temperature of the cavity and is kept constant for 2 hours. After that, the vacuum degree reaches 1.5×10 -3 When Pa, the Hall ion source of the vacuum coating machine was turned on for cleaning. The cleaning time was 6 min. The anode voltage of the Hall ion source was 220 V, the anode current was 1.2-1.5 A, the neutralization current was 1.3-1.5 A, the neutralization gas flow rate was 10 sccm, and the argon gas flow rate accounted for 100%;
[0038] S14, vacuum degree reaches 1.0×10 -3 When the temperature is 0.504°C, a dielectric layer consisting of 291nmGe / 144nmZnS / 671nmGe is deposited on the convex surface of the lens in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers. The Ge film layer is evaporated by electron beam, and the ZnS film layer is evaporated by resistance heating. The deposition rate of the Ge film layer is 0.4nm / s, and the deposition rate of the ZnS film layer is 0.8nm / s. The film layers of the dielectric layer are not deposited by ion source assistance and are deposited at the set temperature of the chamber.
[0040] S15, after the dielectric layer is plated, the cavity is naturally cooled to below 60°C, and the fixture and the lens are taken out;
[0041] S16, placing the lens on the bottom plate of the carbon film machine with the convex surface facing upward;
[0042] S17, carbon film machine vacuum reaches 1.2×10 -3 Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3min, the argon flow rate of the RF ion source is 20sccm, and the power is 600-700W;
[0043] S18, carbon film machine vacuum reaches 6.0×10 -4 Pa starts to deposit DLC film layer, using three-stage deposition.
[0044] The first stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 500s, the RF power supply is started, the RF power supply power is 1200W, and the deposition time is 1400s.
[0046] The second stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 1000s, the RF power supply is started, the RF power supply power is 1000W, and the deposition time is 1400s.
[0048] The third stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 1500s, the RF power supply is started, the RF source power is 800W, and the deposition time is 1400s;
[0049] After the three stages were completed, the thickness of the DLC film was 1280nm;
[0050] S19, after the DLC film is coated, the carbon film machine is cooled for 50-60 minutes, and the door is opened to take out the lens; S2, AR film coating, including sub-steps:
[0051] S21, cleaning the accompanying plated sheet of the chalcogenide glass substrate on which the DLC film layer has been coated on the convex surface of the lens and the surface of the lens product corresponding to the concave surface of the lens;
[0052] S22, placing the cleaned lens into a fixture with the concave surface facing downward, and hanging the fixture with the lens placed into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 130°C;
[0054] S23, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches
[0055] 1.5×10 -3 Pa and the temperature of the chamber reaches the set temperature, turn on the Hall ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2-1.5A, the neutralization current is 1.3-1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%;
[0056] S24, vacuum degree reaches 1.0×10 -3 Pa, 32 layers are plated on the concave surface of the lens.
[0057] An AR film composed of 3nmGe / 250nmZnS / 395nmGe / 741nmZnS / 350nmYbF3 / 285nmZnS, wherein the numbers with nm before Ge, ZnS and YbF3 are the thickness of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer and the YbF3 film layer are evaporated by resistance heating, the deposition rate of the Ge film layer is 0.3nm / s, the deposition rate of the ZnS film layer is 0.8nm / s, and the deposition rate of the YbF3 film layer is 0.6nm / s, and the film layers of the AR film are not deposited by ion source assistance and are deposited at the set temperature of the chamber;
[0058] S25, after the dielectric layer is plated, the cavity is naturally cooled to below 60°C, and the fixture and the lens are taken out.
[0059] In the preparation method of DLC+AR film coated on a chalcogenide glass substrate according to the present disclosure, through step S1 and step S2, by coating the convex surface of the lens of the chalcogenide glass substrate with Sub (chalcogenide glass substrate) / Ge / ZnS / Ge / DLC / AIR (air) film system (i.e., coating DLC) and coating the concave surface of the lens of the chalcogenide glass substrate with Sub (chalcogenide glass substrate) / Ge / ZnS / Ge / ZnS / YbF3 / ZnS / AIR (air) film system (i.e., AR film), as verified by the subsequent test process, the accompanying plate of the chalcogenide glass substrate together with the film systems on both sides can not only achieve an average transmittance of more than 91% (specifically 91.19%) in the 8-12 μm band, but also pass the water bubble test, salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, constant temperature and humidity test, friction resistance test (moderate friction test), low temperature test and high temperature test, so as to meet the use of the window sheet in various environments and meet the requirements of the application end.
[0060] The cleaning of sub-step S11 and sub-step S21 is beneficial to improving the surface state of the corresponding surface of the film layer of the coating film system of the lens, and is helpful to improve the bonding performance between the film system on the corresponding surface and the corresponding surface of the lens. For example, in sub-step S11 and sub-step S21, ultrasonic cleaning is used for cleaning. Specifically, ultrasonic cleaning uses aluminum oxide polishing liquid polishing and then ultrasonic pure water cleaning. For example, the aluminum oxide polishing liquid uses a 0.1μm model polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
[0061] In sub-step S11, for example, the chalcogenide glass is IG06. In step S11, for example, the thickness of the accompanying plating sheet is 2 mm.
[0062] The temperature setting of the vacuum coating machine in sub-step S12 and sub-step S22 heats the lens through the cavity of the coating machine, which helps the growth of the film layer from the lens and reduces the film layer growth stress. In step S12 and sub-step S22, for example, the vacuum coating is Siwork ZZS-1350.
[0063] The ion source cleaning of sub-steps S13, S17 and S23 will remove the impurities and oil molecules adsorbed on the surface of the corresponding surface of the lens, thereby greatly improving the interface state, which is helpful to improve the bonding performance between the film layer and the corresponding surface of the lens. At the same time, cleaning by the ion source can heat the corresponding surface of the lens, which is helpful for the growth of the film layer from the lens and reduces the growth stress of the film layer. In step S13 and sub-step S23, specifically, the anode current of the Hall ion source is 1.2A and the neutralization current is 1.5A. In sub-step S17, specifically, the power of the RF ion source is 650W.
[0064] In sub-step S14, sub-step S18 and sub-step 24, for example, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.99 MHz.
[0065] In sub-step S16, for example, the carbon film machine is a Seawork HLWT700-VII.
[0066] [test]
[0067] Example 1
[0068] The preparation method of the chalcogenide glass substrate coated with DLC+AR film in Example 1 adopts the following steps:
[0069] S1, coating the DLC film layer using the following sub-steps:
[0070] S11, cleaning the convex surface of the accompanying plated sheet and lens product that needs to be coated with a DLC film layer of the chalcogenide glass substrate of the lens, the chalcogenide glass is IG06, the thickness of the accompanying plate is 2mm, and the cleaning is carried out by ultrasonic cleaning, and the ultrasonic cleaning is polished with an aluminum oxide polishing liquid, and then ultrasonic pure water cleaning, and the aluminum oxide polishing liquid is a 0.1μm polycrystalline diamond liquid of Nanjing Henry Precision Optics Co., Ltd.;
[0071] S12, placing the cleaned lens into a fixture with the convex surface facing downward, and hanging the fixture with the lens into the cavity of the vacuum coating machine. The temperature of the cavity is set to 130°C, and the vacuum coating is Siwork ZZS-1350;
[0072] S13, the vacuum coating machine is started, vacuumed and heated, and the temperature of the cavity reaches the set temperature of the cavity and is kept constant for 2 hours. After that, the vacuum degree reaches 1.5×10 -3 Pa, the Hall ion source of the vacuum coating machine was turned on for cleaning. The cleaning time was 6 min, the anode voltage of the Hall ion source was 220 V, the anode current was 1.2 A, the neutralization current was 1.5 A, the neutralization gas flow rate was 10 sccm, and the argon
[0073] The airflow ratio is 100%;
[0074] S14, vacuum degree reaches 1.0×10 -3When the temperature is 0.5040°C, a dielectric layer composed of 291nmGe / 144nmZnS / 671nmGe is deposited on the convex surface of the lens in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer is evaporated by resistance heating, the deposition rate of the Ge film layer is 0.4nm / s, and the deposition rate of the ZnS film layer is 0.8nm / s, each film layer of the dielectric layer is not deposited by ion source assistance and is deposited at the set temperature of the cavity, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillator sheets of the crystal controller, after the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator sheet among the multiple crystal oscillator sheets, and the crystal oscillator frequency is not less than 5.99MHz;
[0075] S15, after the dielectric layer is plated, the cavity is naturally cooled to 60°C, and the fixture and the lens are taken out;
[0076] S16, placing the lens with the convex surface facing upward on the bottom plate of the carbon film machine, the carbon film machine is Siwork HLWT700-VII;
[0077] S17, carbon film machine vacuum reaches 1.2×10 -3 At Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3 min, the argon flow rate of the RF ion source is 20 sccm, and the power is 650 W;
[0078] S18, carbon film machine vacuum reaches 6.0×10 -4 Pa starts to deposit DLC film layer, using three-stage deposition.
[0079] The first stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling (i.e. methane and argon) is delayed for 500s and the RF power is started. The RF power is 1200W.
[0080] The deposition time is 1400s.
[0081] The second stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling (i.e. methane and argon) is delayed for 1000s, the RF power is started, the RF power is 1000W, and the deposition time is 1400s.
[0082] The third stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm,
[0083] The RF power supply is started after a delay of 1500s after filling with gas (i.e. methane and argon). The RF source power is 800W.
[0084] The deposition time was 1400 s;
[0085] After the three stages are completed, the thickness of the DLC film is 1280nm. The film thickness is monitored by using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller using the crystal oscillator method. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5.99MHz.
[0087] S19, after the DLC film is coated, the carbon film machine is cooled for 55 minutes, and the door is opened to take out the lens; S2, the AR film is coated using the following sub-steps:
[0088] S21, cleaning the accompanying plated sheet of the chalcogenide glass substrate with a DLC film layer on the convex surface of the lens and the surface of the lens product corresponding to the concave surface of the lens, using ultrasonic cleaning, and then ultrasonic pure water cleaning with aluminum oxide polishing liquid, and the aluminum oxide polishing liquid uses 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.;
[0089] S22, placing the cleaned lens into a fixture with the concave surface facing downward, and hanging the fixture with the lens into the cavity of the vacuum coating machine. The temperature of the cavity is set to 130°C, and the vacuum coating is Siwork ZZS-1350;
[0090] S23, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches 1.5×10 -3 When the temperature of the chamber reaches the set temperature, the Hall ion source of the vacuum coating machine is turned on for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2A, the neutralization current is 1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%;
[0091] S24, vacuum degree reaches 1.0×10 -3 Pa, 32 layers are plated on the concave surface of the lens.
[0092] AR film composed of 3nmGe / 250nmZnS / 395nmGe / 741nmZnS / 350nmYbF3 / 285nmZnS, wherein the numbers with nm before Ge, ZnS and YbF3 are the thickness of the corresponding film layers. The Ge film layer is evaporated by electron beam, and the ZnS film layer and the YbF3 film layer are evaporated by resistance heating. The deposition rate of the Ge film layer is 0.3nm / s, the deposition rate of the ZnS film layer is 0.8nm / s, and the deposition rate of the YbF3 film layer is 0.6nm / s. The film layers of the AR film are not deposited by ion source assistance and are deposited at the set temperature of the chamber. The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5.
[0093] 99MHz;
[0094] S25, after the dielectric layer is plated, the cavity is naturally cooled to 60°C, and the fixture and the lens are taken out.
[0095] Figure 2 The transmittance curve of the accompanying plate of Example 1 together with the DLC+AR films on both sides in the 8-12 μm band. Figure 2 It can be seen that the transmittance of the accompanying coating sheet of Example 1 together with the films on both sides in the 8-12 μm band is greater than 91% (specifically 91.19%) on average.
[0096] The accompanying plating sheet of Example 1 and the films on both sides were tested as follows.
[0097] Water bubble test: Take tap water to carry out water bubble test for 2 hours, no film system on each side of the accompanying plating sheet is found to fall off from the accompanying plating sheet, and no film system on each side is found to be cracked.
[0098] Salt spray test: After 48 hours of neutral salt spray test, no film peeling or cracking on the surfaces of the accompanying plating sheets was found.
[0099] Adhesion test: Use hand to stick 3M tape on each side of the plating sheet and pull the tape in the direction opposite to the sticking end. The film layer is not pulled up.
[0100] Thermal shock test: In a high and low temperature box, thermal shock was carried out in the range of -40℃ to 85℃ for 24 hours. No film falling off or cracking of the film on each surface of the accompanying plating sheet was found.
[0101] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, no film peeling or cracking of the film on each surface of the accompanying plating sheet was found.
[0102] Friction test (moderate friction test): Wrap the rubber friction head of the friction machine with degreased cloth, apply a pressure of 4.9N on the film surface of the accompanying plating sheet for 50 times (25 back and forth), and no scratches or damage were found on the film surface of each side of the accompanying plating sheet.
[0103] Low temperature test: in a low temperature box, at -40℃ for 48h, no film peeling or cracking of the film on each side of the accompanying plating sheet was found.
[0104] High temperature test: in a high temperature box, at 85℃ for 48h, no film peeling or cracking of the film on each side of the accompanying plating sheet was found.
[0105] That is, the accompanying plating sheet of Example 1 and the film systems on both sides all passed the above eight tests.
[0106] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for preparing a DLC+AR film by coating a chalcogenide glass substrate, characterized in that: Includes steps: S1, coating a DLC film layer, including sub-steps: S11, cleaning the convex surface of the accompanying plated sheet and lens product which needs to be coated with a DLC film layer as a chalcogenide glass substrate of the lens; S12, placing the cleaned lens into a fixture with the convex surface facing downward, and hanging the fixture with the lens placed into the cavity of the vacuum coating machine, and setting the temperature of the cavity to 130°C; S13, the vacuum coating machine is started, vacuumed and heated, and the temperature of the cavity reaches the set temperature of the cavity and is kept constant for 2 hours. After that, the vacuum degree reaches 1.5×10 -3 When Pa, the Hall ion source of the vacuum coating machine was turned on for cleaning. The cleaning time was 6 min. The anode voltage of the Hall ion source was 220 V, the anode current was 1.2-1.5 A, the neutralization current was 1.3-1.5 A, the neutralization gas flow rate was 10 sccm, and the argon gas flow rate accounted for 100%; S14, vacuum degree reaches 1.0×10 -3 When the temperature is 0.504°C, a dielectric layer consisting of 291nmGe / 144nmZnS / 671nmGe is deposited on the convex surface of the lens in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers. The Ge film layer is evaporated by electron beam, and the ZnS film layer is evaporated by resistance heating. The deposition rate of the Ge film layer is 0.4nm / s, and the deposition rate of the ZnS film layer is 0.8nm / s. The film layers of the dielectric layer are not deposited by ion source assistance and are deposited at the set temperature of the chamber. S15, after the dielectric layer is plated, the cavity is naturally cooled to below 60°C, and the fixture and the lens are taken out; S16, placing the lens on the bottom plate of the carbon film machine with the convex surface facing upward; S17, carbon film machine vacuum reaches 1.2×10 -3 Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3min, the argon flow rate of the RF ion source is 20sccm, and the power is 600-700W; S18, carbon film machine vacuum reaches 6.0×10 -4 Pa starts to deposit DLC film layer, using three-stage deposition. The first stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 500s, the RF power supply is started, the RF power supply power is 1200W, and the deposition time is 1400s. The second stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the filling delay is 1000s, the RF power supply is started, the RF power supply power is 1000W, and the deposition time is 1400s. The third stage of plating: the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, The RF power supply was started after a gas filling delay of 1500s, the RF source power was 800W, and the deposition time was 1400s; After the three stages were completed, the thickness of the DLC film was 1280nm; S19, after the DLC film is deposited, the carbon film machine is cooled for 50-60 minutes, and the door is opened to take out the lens; S2, coating an AR film, including sub-steps: S21, cleaning the accompanying plated sheet of the chalcogenide glass substrate on which the DLC film layer has been coated on the convex surface of the lens and the surface of the lens product corresponding to the concave surface of the lens; S22, put the cleaned lens into the fixture with the concave surface facing downward. The fixture with the lens is hung into the chamber of the vacuum coating machine, and the temperature of the chamber is set to 130°C; S23, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches 1.5×10 -3 Pa and the temperature of the chamber reaches the set temperature, turn on the Hall ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2-1.5A, the neutralization current is 1.3-1.5A, and the neutralization gas flow rate is 10sccm. The argon flow rate accounts for 100%; S24, vacuum degree reaches 1.0×10 -3 When the temperature is 0.500°C, an AR film composed of 323nmGe / 250nmZnS / 395nmGe / 741nmZnS / 350nmYbF3 / 285nmZnS is deposited on the concave surface of the lens in sequence, wherein the numbers with nm before Ge, ZnS and YbF3 are the thicknesses of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer and the YbF3 film layer are evaporated by resistance heating, the deposition rate of the Ge film layer is 0.3nm / s, the deposition rate of the ZnS film layer is 0.8nm / s, and the deposition rate of the YbF3 film layer is 0.6nm / s, and the film layers of the AR film are not deposited by ion source assistance and are deposited at the set temperature of the chamber; S25, after the dielectric layer is plated, the cavity is naturally cooled to below 60°C, and the fixture and the lens are taken out.
2. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In sub-step S11 and sub-step S21 , ultrasonic cleaning is used for cleaning.
3. The method for preparing a DLC+AR film by coating a chalcogenide glass substrate according to claim 2, characterized in that: Ultrasonic cleaning uses aluminum oxide polishing liquid for polishing, followed by ultrasonic pure water cleaning. The alumina polishing liquid adopts the 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
4. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In sub-step S11, the chalcogenide glass is IG06.
5. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In step S11, the thickness of the accompanying plating sheet is 2 mm.
6. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In step S12 and sub-step S22, the vacuum coating is Siwork ZZS-1350.
7. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In step S13 and sub-step S23, the anode current of the Hall ion source is 1.2A and the neutralization current is 1.5A.
8. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In sub-step S14, sub-step S18 and sub-step 24, The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.99MHz.
9. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In sub-step S16, the carbon film machine is a Siwork HLWT700-VII.
10. The method for preparing a DLC+AR film coated on a chalcogenide glass substrate according to claim 1, characterized in that: In sub-step S17, the power of the RF ion source is 650W.